Effects of Goat Manure, Biochar, and NPK Applications on Growth and Nutrient Concentrations of Lettuce - Ali İnal; Mehmet Burak Taşkın; Emre Can Kaya; Moustapha Maman Mounırou; Hamidou Taffa Abdoul-azize (Journal of Agricultural Sciences)
During the last decades, biochar (BC) gained increasing importance amongst scholars. Though, only a few studies explored the effects of the combined application of BC with manure on plant growth and nutrient concentrations. This study investigates the effects of separate and joint applications of goat manure (GM) and its derived BC on the growth and mineral element concentrations in lettuce. A completely random design was used in the field experiment. Two factors consisted of GM, BC at 5 Mg ha-1 and 10 Mg ha-1 combined with inorganic fertilizers [nitrogen, phosphorus, and potassium (NPK)] at 100%, 50%, and 0% were applied to the soil before planting the lettuce and, ANOVA analysis and Duncan test (at α=5%) were conducted. The results showed that a joint application of inorganic and organic fertilizers affects significantly the yield and yield parameters of the lettuce whilst the separate application of organic fertilizer affects significantly the lettuce content in N, P, K, Ca and Mg. Compared to GM, the application of GM-derived BC increases significantly the lettuce content in Zn and decreases its content in Cu. In addition, the highest total yield of lettuce was obtained with a joint combination of GM, BC, and 100% NPK (100 kg N ha-1, 100 kg P2O5 ha-1 and 100 kg K2O ha-1). Consequently, this combination of organic and inorganic fertilizers is favorable fertilization in producing lettuce.